2018
DOI: 10.2478/plc-2018-0014
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Executive Functions and Literacy Among Children With Specific Language Impairment

Abstract: Recently, extensive studies investigating executive functions in children with specific language impairment (SLI) have been performed. In the present study, we compared the level of executive functions (i.e., inhibitory control and cognitive flexibility) and literacy skills between 53 healthy children and 53 children with SLIs between the ages of 3 and 11 years. The groups were matched by age, gender and parental education level. Executive functions were assessed using the Children Card Sort, and the Literacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Several studies that have compared DCCS performance between children with and without DLD have found significantly better performance for typically developing children relative to the DLD group. 14,43,44 However, using this same task, Reichenbach et al 45 reported equivalent performance between DLD and typically developing groups. Yang and Gray 33 found no group differences in a nonverbal version of the DCCS, but reported that children with DLD performed significantly worse than typically developing peers on a verbal version of DCCS that required labeling.…”
Section: Shiftingmentioning
confidence: 94%
“…Several studies that have compared DCCS performance between children with and without DLD have found significantly better performance for typically developing children relative to the DLD group. 14,43,44 However, using this same task, Reichenbach et al 45 reported equivalent performance between DLD and typically developing groups. Yang and Gray 33 found no group differences in a nonverbal version of the DCCS, but reported that children with DLD performed significantly worse than typically developing peers on a verbal version of DCCS that required labeling.…”
Section: Shiftingmentioning
confidence: 94%